1985
DOI: 10.7589/0090-3558-21.3.264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Season and Physical Condition on the Gastrointestinal Helminth Community of White-Tailed Deer From the Texas Edwards Plateau

Abstract: Eighty-six adult female white-tailed deer, Odocoileus virginianus (Zimmermann), collected over a 12-mo period in the Texas Edwards Plateau, harbored six species of nematodes (Haemonchus contortus, Gongylonema pulchrum, Oesophagostomum venulosum, Ostertagia ostertagi, Cooperia sp., and Apteragia odocoilei), and two cestodes (Moniezia sp. and Taenia hydatigena). The patterns of distribution of the three common species of gastrointestinal helminths (H. contortus, O. venulosum, and G. pulchrum) were overdispersed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…rarely exceed several hundred, with a maximum near 4000 for Ostertagia spp. (e.g., Prestwood and Pursglove 1981;Waid et al 1985;Conti and Howerth 1987;Belem et al 1993). Similar .…”
Section: Monodontus Louisianensismentioning
confidence: 99%
See 1 more Smart Citation
“…rarely exceed several hundred, with a maximum near 4000 for Ostertagia spp. (e.g., Prestwood and Pursglove 1981;Waid et al 1985;Conti and Howerth 1987;Belem et al 1993). Similar .…”
Section: Monodontus Louisianensismentioning
confidence: 99%
“…Specifically, management was tied to enhancing nutrition and natural immunity while reducing environmental contamination and minimizing the potential for transmission of parasites and related density-dependent disease conditions (Eve 1981). This procedure has been employed with mixed success in the southeastern United States, and its application to other regions has been problematic due to seasonal fluctuations in the abundance of parasites (Demarias et al 1983;Waid et al 1985). In Norway, Bye (1987) postulated an association linking poor physical condition, high population density, and highintensity infections by ostertagiine nematodes in reindeer.…”
Section: )mentioning
confidence: 99%
“…Host-parasite interactions may not always be clearly evident, thus leading to contradictory interpretations. Furthermore, the use of macroparasites as an index of population health, in particular, counts of gastrointestinal helminths, has often been criticized (Demarais et al, 1983;Waid et al, 1985;Rossi et al, 1997; Pérez et al, 2003). Nevertheless, different studies have demonstrated that parasites can have an impact on health status in natural ruminant populations (e.g., Gulland, 1992;Stien et al, 2002), and further data, both from an ecological perspective and a management point of view, are needed.…”
mentioning
confidence: 99%
“…Gastrointestinal helminths of black bear are examined from four localities in the southeastern United States (Pence et al, 1983). Data on abomasal helminths of white-tailed deer from the coastal plain of Georgia and mesic areas of Arkansas and Louisiana along the Mississippi River floodplain are from records of the Southeastern Cooperative Wildlife Disease Study (University of Georgia, Athens, GA); deer from central and western Texas are from Waid et al (1985) and Stubblefield et al (1987), respectively. Data on abomasal helminths of white-tailed deer from the coastal plain of Georgia and mesic areas of Arkansas and Louisiana along the Mississippi River floodplain are from records of the Southeastern Cooperative Wildlife Disease Study (University of Georgia, Athens, GA); deer from central and western Texas are from Waid et al (1985) and Stubblefield et al (1987), respectively.…”
Section: Study Sites and Analysis Of Datamentioning
confidence: 99%